Identifying mountain permafrost degradation by repeating historical electrical resistivity tomography (ERT) measurements - Buckel, Johannes; Mudler, Jan; Gardeweg, Rainer; Hauck, Christian; Hilbich, Christin; Frauenfelder, Regula; Kneisel, Christof; Buchelt, Sebastian; Blöthe, Jan Henrik; Hördt, Andreas; Bücker, Matthias (The Cryosphere, 2023)
Ongoing global warming intensifies the degradation of permafrost. Permafrost thawing impacts landform evolution, reduces freshwater resources, enhances the potential of natural hazards and thus has significant socio-economic impacts. Electrical resistivity tomography (ERT) has been widely used to map the ice-containing permafrost by its resistivity contrast compared to the surrounding unfrozen medium. This study aims to reveal the effects of ongoing climate warming on mountain permafrost by repeating historical ERT and analyzing the temporal changes in the resistivity distribution. In order to facilitate the measurements, we introduce and discuss the employment of textile electrodes. These newly developed electrodes significantly reduce working effort, are easy to deploy on blocky surfaces and yield sufficiently low contact resistances. We analyze permafrost evolution on three periglacial landforms (two rock glaciers and one talus slope) in the Swiss and Austrian Alps by repeating historical surveys after 10, 12 and 16 years, respectively. The resistivity values have been significantly reduced in ice-poor permafrost landforms at all study sites. Interestingly, resistivity values related to ice-rich permafrost in the studied active rock glacier partly increased during the studied time period. To explain this apparently counterintuitive (in view of increased resistivity) observation, geomorphological circumstances, such as the relief and increased creep velocity of the active rock glacier, are discussed by using additional remote sensing data. The present study highlights ice-poor permafrost degradation in the Alps resulting from ever-accelerating global warming.